Variable posttranslational modifications of severe acute respiratory syndrome coronavirus 2 nucleocapsid protein. (13th May 2021) - Supekar, Nitin T; Shajahan, Asif; Gleinich, Anne S; Rouhani, Daniel S; Heiss, Christian; Chapla, Digantkumar Gopaldas; Moremen, Kelley W; Azadi, Parastoo
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which causes coronavirus disease 2019 (COVID-19), started in 2019 in China and quickly spread into a global pandemic. Nucleocapsid protein (N protein) is highly conserved and is the most abundant protein in coronaviruses and is thus a potential target for both vaccine and point-of-care diagnostics. N Protein has been suggested in the literature as having posttranslational modifications (PTMs), and accurately defining these PTMs is critical for its potential use in medicine. Reports of phosphorylation of N protein have failed to provide detailed site-specific information. We have performed comprehensive glycomics, glycoproteomics and proteomics experiments on two different N protein preparations. Both were expressed in HEK293 cells; one was in-house expressed and purified without a signal peptide (SP) sequence, and the other was commercially produced with a SP channeling it through the secretory pathway. Our results show completely different PTMs on the two N protein preparations. The commercial product contained extensive N- and O-linked glycosylation as well as O-phosphorylation on site Thr393. Conversely, the native N Protein model had O-phosphorylation at Ser176 and no glycosylation, highlighting the importance of knowing the provenance of any commercial protein to be used for scientific or clinical studies. Recent studies have indicated that N protein can serve as an important diagnostic marker for COVID-19 and as a major immunogen by priming protective immune responses. Thus, detailed structural characterization of N protein may provide useful insights for understanding the roles of PTMs on viral pathogenesis, vaccine design and development of point-of-care diagnostics.